Restorative justice as an Effort to Resolve Minor Criminal Cases in Indonesian Criminal Law: Contextualization of Samagama Sutta - Warsito, Warsito; Pangestu, Ilham Aji (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2025)
Criminal law policy regulating minor crimes is an urgent issue that needs resolution. The Restorative justice approach in the contextualization of Samagama Sutta is a relevant reference for future research. Resolving cases by prioritizing peace and victim recovery is an appropriate step for out-of-court settlements. Restorative justice as a criminal procedure can be applied through dialogue or deliberation, resulting in an agreement that does not harm either the victim or the perpetrator. This study aims to identify a model of the Restorative justice approach in resolving minor crimes within the context of the Samagama Sutta. This research employs normative legal research, also known as doctrinal research, which involves examining literature and secondary data, including primary, secondary, and tertiary legal materials. The data collection method used is library research, which involves collecting, identifying, classifying, and analyzing data for citation purposes. The data analysis follows the Peter Mahmud Marzuki model. The study results indicate that minor criminal cases should be resolved outside the court by seeking peaceful solutions through agreements between perpetrators and victims. Penal mediation, from a philosophical perspective, applies the win-win solution principle. It serves as an alternative to criminal case resolution that is simple, fast, and cost-effective. This approach aligns with the Samagama Sutta, which emphasizes the relationship between perpetrators and victims through the dispute resolution method (adikarana samatha), ensuring that peace efforts occur as early as possible.